SISTEM INFORMASI AKUNTANSI PENJUALAN, PEMBELIAN DAN PERSEDIAAN BAHAN BAKU SEBAGAI PENGENDALIAN INTERNAL PERCETAKAN DUTRA DIGITAL PRINTING KABUPATEN KEDIRI - Lestari, Novi Puji; Nurdiwati, Diah; Kurniawan, Andy (Universitas Nusantara PGRI Kediri, 2022)
The background of this study is information systems accounting, because information systems accounting are very important for companies and every company must implement information systems accounting appropriately. The purpose of this study is to analyze how Dutra Digital Printing Implements an information systems accounting for sales, purchasing and inventorying raw materials. This method of research is qualitative. Procedures for collecting data by observation, interviews and documentation of the research subject. This study found that the information systems accounting of Dutra Digital Printing Printing is still not appropriate, with overlapping employee duties and responsibilities that can lead to the accumulation of tasks and lack of detailed documents and record integrity so that it can lead to data manipulation.